POVERTY LEVELS MUST BE REDUCED TO IMPROVE ACCESSIBILITY TO HEALTH SERVICES - Yesi, Desri; Retnaningsih, Ekowati; Sihombing, Pardomuan Robinson; Nuryanto, Nuryanto; Novitha, Irni (Universitas Airlangga, 2024)
Background: Access to health services is a fundamental right for every citizen, but its equitable distribution remains challenging due to the influence of several variables. Indonesia has achieved Universal Health Coverage (UHC), but access to health services for those with health problems is still low. Aims: This study aims to determine the variables influencing access to health services in Indonesia. Methods: Longitudinal analysis of panel data was used, and the dataset was taken from the 34 provinces of Indonesia from 2018 to 2022. The data obtained were then analyzed descriptively and analytically by linear regression using STATA software. Results: Individual and family variables influencing access to health services for the population with health problems included variable need (health problem), ownership of health insurance, and ability to pay. Furthermore, the results showed that the number of areas with high poverty rates (socioeconomic) was a contextual factor with a higher level of influence. Conclusion: Based on the results, policies to improve access to health services, a basic human right, could not be solely achieved by the health sector. Therefore, integrated comprehensive planning collaboration of Penta-Helical elements was needed to reduce poverty enclaves. Keywords: ability to pay, access to health services, health insurance, poverty